Mechanical, wear, and fracture behavior of Titanium Diboride (TiB2) - Cerium Oxide (CeO2) reinforced Al-6061 hot-rolled hybrid composites - S. R. Sreenivasa Iyengar; D. Sethuramu; M. Ravikumar (Fracture and Structural Integrity)
Development of aluminium composites by stircasting technique is an effective method for fabrication of better quality of MMCs. Stircasting technique is one of the most commonly accepted techniques. In this research work, Al6061 / TiB2+CeO2 hybrid MMCs have been fabricated with varying wt. % of TiB2 (2.5%, 5%, 7.5% and 10%) particulates and constant 5% of CeO2 particulates. The monolithic alloy and hybrid composite were hot-rolled at a temperature of 515C. Both the monolithic and hot-rolled hybrid composites were subjected to micro-structural study, hardness and tensile test. Optical microscope analysis revealed uniform dispersal of hard particles within the base matrix in case of both of ascast and hot-rolled composites. Both ascast and hotrolled hybrid composites showed extensive enhanced mechanical behavior and high wear resistance when compared with monolithic alloy. Hot rolled MMCs showed enhancement of 25 % of hardness when compared with monolithic alloy with increasing reinforcement of 2.5 - 10 wt. % of TiB2 content. Tensile strength increased by 53.54 % for hot rolled composites when compared to the as cast and other hybrid composites. Tensile and wear fractography outcome showed internal fractured structure of a tensile and wear specimen which was analysed using SEM analysis.